Expression of proliferation markers in laryngeal squamous cell carcinoma: an association with clinico-pathological factors and treatment outcomes - Iype, Elizabeth Mathew; Balakrishna, Rajan; Subhadradevi, Lakshmi; Thulaseedharan, Jissa Vinoda; Veerabadhran, Bharath; Kattoran, Jayasree (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The study was done with the objective to study the expression of epidermal growth factor receptor (EGFR), cyclin D1 and Ki-67 in laryngeal squamous cell carcinoma and to assess the correlation of all three proliferation markers with various clinic-pathological parameters, the treatment outcomes as well as survival. Methods: We prospectively evaluated the surgical specimens of 72 laryngeal squamous cell carcinoma (LSCC) patients, treated with primary surgery and post-operative adjuvant therapy. Tumor tissue samples were analysed for the expression of EGFR, cyclin D1 and Ki-67 markers and analysis were done by immune-histochemistry and western blot test. Results: EGFR showed significant expression in 67.6% and was insignificant in 31.9% patients in our analysis of 72 tumor samples. Cyclin D1 showed intense expression in 43%, and was insignificant in 57% patients. Ki-67 was intensely expressed in 43% patients. There was no correlation between expression of these markers with age, T-stage and N-stage. However, all the three markers showed significantly intense expression in tumours with extra capsular disease as well as perineural invasion (PNI) both of which are features of invasiveness of the tumor. Conclusions: Estimation of biomarkers such as EGFR, cyclin Dl, and Ki-67 could be beneficial in predicting tumor aggressiveness, prognosis and survival in LSCC patients. Thus, all the three proliferation markers can be categorized as markers of invasiveness. Combination of proliferation markers-EGFR, cyclin D1 and Ki-67 is useful pre-operatively in planning surgical strategies so as to decide a more radical approach for the resection of the primary as well as neck dissection.